2009
DOI: 10.1073/pnas.0806742106
|View full text |Cite
|
Sign up to set email alerts
|

PPARα blocks glucocorticoid receptor α-mediated transactivation but cooperates with the activated glucocorticoid receptor α for transrepression on NF-κB

Abstract: Glucocorticoid receptor ␣ (GR␣) and peroxisome proliferatoractivated receptor ␣ (PPAR␣) are transcription factors with clinically important immune-modulating properties. Either receptor can inhibit cytokine gene expression, mainly through interference with nuclear factor B (NF-B)-driven gene expression. The present work aimed to investigate a functional cross-talk between PPAR␣-and GR␣-mediated signaling pathways. Simultaneous activation of PPAR␣ and GR␣ dose-dependently enhances transrepression of NF-B-driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 24 publications
5
76
1
2
Order By: Relevance
“…Furthermore, future experiments using electro mobility shift assays (EMSA) or PPAR-responsive elements (PPRE) luciferase-tagged promoter assays have to finally prove whether PEA increases PPAR-alpha DNA binding and PPAR-alpha transcription factor activity in neurons and/or microglial cells as it has previously been shown for other potent PPAR-alpha agonists like fibrates or Wy-14,643 (Kleemann et al 2003;Bougarne et al 2009). …”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, future experiments using electro mobility shift assays (EMSA) or PPAR-responsive elements (PPRE) luciferase-tagged promoter assays have to finally prove whether PEA increases PPAR-alpha DNA binding and PPAR-alpha transcription factor activity in neurons and/or microglial cells as it has previously been shown for other potent PPAR-alpha agonists like fibrates or Wy-14,643 (Kleemann et al 2003;Bougarne et al 2009). …”
Section: Discussionmentioning
confidence: 96%
“…A possible cross-talk mechanism between PPARα and the glucocorticoid (GC) pathway has been shown in HepG2 cells. Dexamethasone (a synthetic glucocorticoid) activates GC receptor-α (GRα) by eliciting a conformational change [13]. Activated GRα can directly regulate the expression of its target genes through binding promoters containing the GC response element (GREs).…”
Section: Pparαmentioning
confidence: 99%
“…28) Although it is not clear whether and how the above activities of 3 are linked to the inflammatory system, our study revealed that 3 suppresses the TNF-a and NO production in LPS-stimulated immune cells, demonstrating one new aspect for the various pharmacological functions of 3. Since 3 suppresses not only TNF-a but also IL-6 that plays an important role in chronic inflammation, 29) this compound would be a promising lead in developing new agents for treatment of chronic inflammatory diseases such as rheumatoid arthritis.…”
Section: Resultsmentioning
confidence: 98%